Occupational contact urticaria: lessons from the French National Network for Occupational Disease Vigilance and Prevention (RNV3P)3. (26th October 2015) - Bensefa‐Colas, L.; Telle‐Lamberton, M.; Faye, S.; Bourrain, J.‐L.; Crépy, M.‐N.; Lasfargues, G.; Choudat, D.; ,; Momas, I.
Summary: Background: Occupational contact urticaria (OCU) is an occupational contact dermatitis that can cause serious health consequences and disability at work. Objectives: To describe OCU and its temporal trends by the main causal agents and activity sectors in a nationwide scheme in France. Methods: Using data from the French National Network for Occupational Disease Vigilance and Prevention (RNV3P), we described OCU reported during the period 2001–10 and analysed the temporal trends of OCU and OCU attributed to the most frequent agents over the study period. Trends analyses were supported by reporting odds ratios using a logistic regression model with reference to 2001, or with time as a continuous variable. Results: During the study period, 251 cases of OCU were reported in RNV3P, half of which were due to natural rubber latex, in particular in the health and social work activity sector (HSW). The number of these cases declined significantly over the study period (19% per year), and particularly after 2006. Conversely, the other causes of OCU did not decrease. Conclusions: Using surveillance data from a French national network, this study has found that there was a significant decline in OCU due to natural rubber latex, particularly in the HSW, when powdered latex gloves were banned from French hospitals. Our results show the effectiveness of this preventive measure, and suggest that this practice should be extended to other sectors. Abstract : What's already known about this topic? Contact urticaria is known to be a frequent cause of occupational dermatosis, but statistics on occupational contact urticaria (OCU) are scarce. What does this study add? For the first time, temporal trends in OCU were studied over a 10‐year period using data from the French RNV3P network. The results show the effectiveness of latex exposure prevention measures for healthcare workers and the need for these measures to be extended to other sectors to reduce OCU in the workplace. Linked Comment: Chowdhury, Br J Dermatol 2015; 173: 1364–65 .